How well do Computers Solve Math Word Problems? Large-Scale Dataset Construction and Evaluation - Huang, Danqing; Shi, Shuming; Lin, Chin-Yew; Yin, Jian; Ma, Wei-Ying (Meeting of the Association for Computational Linguistics, 2016)
Recently a few systems for automatically solving math word problems have reported promising results. However, the datasets used for evaluation have limitations in both scale and diversity. In this paper, we build a large-scale dataset which is more than 9 times the size of previous ones, and contains many more problem types. Problems in the dataset are semi-automatically obtained from community question-answering (CQA) web pages. A ranking SVM model is trained to automatically extract problem answers from the answer text provided by CQA users, which significantly reduces human annotation cost. Experiments conducted on the new dataset lead to interesting and surprising results.